Penguatan Ekonomi Lokal melalui Bazar UMKM yang Terintegrasi dengan Pagelaran Budaya: Implementasi Pendekatan ABCD di Desa Puhjarak - Nadiroh, Laili; Aria, Vellani; Kurniawan, Muhammad Wahyu; Irawan, Mazida Aulia; Mulyaningrum, Nabilla (Yayasan Mutiara Hati Moeslem, 2025)
This research focuses on the importance of MSME to the rural economy in Indonesia, which often faces challenges in marketing, digitalization, and promotion. Aiming to increase exposure of MSME products in Puhjarak Village, this study integrated an MSME Bazaar with arts performances and wayang performances. The method used was an asset-based approach (ABCD), involving the village government, community, and students in planning and evaluation. The results showed a 60-70% increase in sales turnover and follow-up orders. This activity not only expanded marketing networks and social solidarity but also successfully preserved local culture. In conclusion, combining a bazaar with performing arts is an effective strategy to increase the competitiveness of MSME.